DC sputtered WTi nanoparticles for solar thermal absorption: Synthesis and characterization - Abbas AL-Rjoub (Next Nanotechnology, 2025)
This study presents a method for tungsten-titanium (WTi) nanoparticles synthesis by DC-magnetron sputtering in a plasma gas condensation cluster-source at room temperature. After optimizing the conditions for nanoparticles formation, the samples were extensively characterized through Scanning-Electron Microscopy (SEM), Energy Dispersive X-Ray Spectroscopy (EDS), X-ray Diffraction (XRD), and Transmission-Electron Microscopy (TEM). For nanoparticles produced under a partial Ar pressure of 14 SCCM, the synthesis rate for thick layer on Si is 241 nm/min. The diameters of nanoparticles deposited on CF 400-Cu grids ranged from 30 nm to 55 nm. The morphology of the nanoparticles is distinguished by a dendritic, flower-like structure, with significant agglomeration observed in particles of varying sizes. TEM and XRD analysis confirm that the nanoparticles exhibit a crystalline-structure, predominantly in the α-W phase. The embedded WTi nanoparticles in SiAlOx layer with variation in current density from 2.6 mA/cm² to 7.8 mA/cm² provide a wide range of transmittance (T) and reflectance (R) values with specific optical constants refractive index (n) and extinction coefficient (k) for tailored optical applications, capable to simulate a solar thermal absorber with absorptance (α) of 96.0 %.